PENGARUH UMR DAN PENDUDUK MISKIN TERHADAP TINGKAT PDRB DI PROVINSI SUMATERA UTARA - Selian, Julaidi; Tampubolon, Kezia Angelica; Hasibuan, Robiatun Adawiyah (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This study aims to analyze the effect of the minimum wage and the poor on GRDPin the province of North Sumatra in the period 2001 to 2020. This study usesmultiple regression analysis. Based on the results of the regression analysis, thepopulation variable has a positive and significant effect on GRDP, and the PoorPopulation variable has a negative and significant effect on GRDP in NorthSumatra Province. Simultaneously, the two independent variables have asignificant relationship with GRDP in North Sumatra Province.